THE ESSENCE AND CONTENT OF THE COMMUNICATIVE COMPONENT OF READINESS OF FUTURE MANAGERS TO CREATE A HEALTH-ORIENTED ENVIRONMEN OF THE ORGANIZATION - Zavydivska, Olga (International Journal of Innovative Technologies in Social Science, 2020)
The essence and content of communicative component of the readiness of future managers to create a health-oriented environment of the organization are substantiated. The communicative abilities of future managers are characterized. The change of communication types inherent future managers before and after the experiment is analyzed. The dynamics of qualitative changes in the levels of formation of the communicative component in control and experimental groups of students before and after the experiment is presented.It is declared that health-oriented managerial behavior of future managers, their activities related to the dissemination of information about the effectiveness of health-preserving technologies in the work environment depend on their communicative abilities. The results of the introduction of the author's complementary-integrative pedagogical technology of formation the readiness of future managers to create a health-oriented environment of the organization in terms of influences on the development of their communication skills are presented. The obtained experimental data allow us to conclude that the absolute average value of qualitative changes in the level of the communicative component after the experiment in the experimental groups of students is higher compared to control groups of students (by 14.4%), and the coefficient of efficiency is 12.52%. This fact indicates the effectiveness of the implemented complementary-integrative pedagogical technology of formation of future managers' readiness to create a health-oriented environment of the organization.